Genesis of Hydrothermal Geothermal System and Evaluation of Resources: A Case Study of Pingdingshan Coalfield, China - Yanhe Li; Zheng Zhen; Zhijun Wan; Peng Shi; Yuan Zhang (Geofluids)
As one of the clean renewable energy sources, geothermal energy has broad prospects, and correctly understanding its genetic mechanism and resource reserve is the basis for the efficient utilization of the geothermal resources. The characteristics of the ground temperature field in the Pingdingshan mining area are analyzed, and the influence of groundwater convection in the Karst layer on the formation temperature was carried out by the hydrothermal coupling. In addition, the Monte Carlo method is adopted to reduce the uncertainty of input parameters. Results show that the geothermal field distribution shows obvious zoning characteristics, and the hydrothermal coupling simulation shows that the water-conducting fault can profoundly change the distribution of formation temperature, which is the boundary for the decline or rise of formation temperature. The thermal refraction effect caused by the fluctuation of bedrock is the main reason for the high temperature in the structural uplift area of the mining area, which is the heat flow disturbance caused by the thermal refraction effect within 12.3 mW/m2. The heat contained in geothermal resources is 5.037~15.82×1014 J, while the heat contained in geothermal water is 0.8806~6.531×1014 J, and the rest is contained in the rock matrix.